INTERFERENCE AND DIFFRACTION SIMULATION WITH MATLAB PROGRAMMING - (NIM 20206024), MUSAHIR
Interference and diffraction area nature phenomena that occur in the dailey lifes and be one of physics research, especially in optic. Interference is superposition of two or more wave of light. And diffraction is spreading of light direction when a fold of wave through a narrow tight slit. The objectif of this research are to build an interference pattern for N number of slit and diffraction pattern with fft ( Fast Fourier Transform). The diffraction pattern that occur in the computer screen, then be applied to obtain information that required to enhance understanding the phenomenon. The building of light interference simulations based on numerik analysis by using of number complex. The input a wave length input, the distance of slit,and the amount of slit. By using diffraction of amount of slits, will occure primary max, secondary max and minimum point. Building of light interference simulation are based on numeric analisis too. The slit was modeled by array that sign as 1 for aperture and 0 for the opposite. The diffraction on the slit was representations by Fourier Transform, in Matlab software was provided by FFT function. With same command of FFT are obtained diffractions pattern for various appertures. From interference simulation was obtained dark light pattern that expressing max and mn intensity. For interference with N number of slit was obtained N-1 of minimum amount and N-2 of second max amount. From single slit simulations was obtained dark light pattern. The narrower the slit, the wider the light pattern. For circle,the smaller the radius the wider diffraction pattern.